Limited Nuclear Weapons Free Zone-Northeast Asia: Overview - Gourley, Bernard (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.30 Mongolian Journal of International Affairs No.14 2007 pp.102-105